Mengimplementasikan Nilai-nilai Lapang Dada dalam Kajian Hadits - Rohmawan, Fenki; A, Alifya; Alif, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Spacious chest must have a big soul. In practice, have the courage to face shortcomings, respect differences and think broadly. The purpose of this research is to examine the values of spaciousness in hadith studies. So that it can practice these values to follow up what happened through certain conditions and situations. The research method uses a qualitative approach with the library search method, namely collecting data through previous journals as well as primary sources originating from Mashadir Ashliyah Hadith. and the use of thematic hadith methods. The results of this study can be concluded that, broad chest is the result of training ourselves to various conditions and situations, to create positive thoughts, open-mindedness and not to get upset in various kinds of problems.